Variations in wood anatomy in Afrotropical trees with a particular emphasis on radial and axial parenchyma - Plavcová, Lenka; Jandová, Veronika; Altman, Jan; Liancourt, Pierre; Korznikov, Kirill; Doležal, Jiří (Annals of botany, 2024)
BACKGROUND AND AIMS: Understanding anatomical variations across plant phylogenies and environmental gradients is vital for comprehending plant evolution and adaptation. Previous studies on tropical woody plants have paid limited attention to quantitative differences in major xylem tissues, which serve specific roles in mechanical support (fibres), carbohydrate storage and radial conduction (radial parenchyma, rays), wood capacitance (axial parenchyma) and water transport (vessels). To address this gap, we investigate xylem fractions in 173 tropical tree species spanning 134 genera and 53 families along a 2200-m elevational gradient on Mount Cameroon, West Africa. METHODS: We determined how elevation, stem height and wood density affect interspecific differences in vessel, fibre, and specific axial (AP) and radial (RP) parenchyma fractions. We focus on quantifying distinct subcategories of homogeneous or heterogeneous rays and apotracheal, paratracheal and banded axial parenchyma. KEY RESULTS: Elevation-related cooling correlated with reduced AP fractions and vessel diameters, while fibre fractions increased. Lower elevations exhibited elevated AP fractions due to abundant paratracheal and wide-banded parenchyma in tall trees from coastal and lowland forests. Vasicentric and aliform AP were predominantly associated with greater tree height and wider vessels, which might help cope with high evaporative demands via elastic wood capacitance. In contrast, montane trees featured a higher fibre proportion, scarce axial parenchyma, smaller vessel diameters and higher vessel densities. The lack of AP in montane trees was often compensated for by extended uniseriate ray sections with upright or squared ray cells or the presence of living fibres. CONCLUSIONS: Elevation gradient influenced specific xylem fractions, with lower elevations showing elevated AP due to abundant paratracheal and wide-banded parenchyma, securing greater vessel-to-parenchyma connectivity and lower embolism risk. Montane trees featured a higher fibre proportion and smaller vessel diameters, which may aid survival under greater environmental seasonality and fire risk.
Keywords: xylem; stromy; tropické klima; Wood; Axial parenchyma; storage; Cameroon; Trees; Kamerun; xylém; Altitude; Tropical Climate; wood; dřevo; ray parenchyma; tropics; nadmořská výška; capacitance; Xylem